2012
DOI: 10.1140/epjp/i2012-12064-4
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type-II models in the presence of perfect fluid and anisotropic dark energy

Abstract: Spatially homogeneous but totally anisotropic and non-flat Bianchi type II cosmological model has been studied in general relativity in the presence of two minimally interacting fluids; a perfect fluid as the matter fluid and a hypothetical anisotropic fluid as the dark energy fluid. The Einstein's field equations have been solved by applying two kinematical ansätze: we have assumed the variation law for the mean Hubble parameter that yields a constant value of deceleration parameter, and one of the components… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Kumar and Akarsu [54] showed that the anisotropy of the dark energy is constrained to be axially symmetric considering Bianchi type-II models.…”
Section: Preliminaries: Dark Energy Scenariomentioning
confidence: 99%
“…Kumar and Akarsu [54] showed that the anisotropy of the dark energy is constrained to be axially symmetric considering Bianchi type-II models.…”
Section: Preliminaries: Dark Energy Scenariomentioning
confidence: 99%
“…where p and  are the pressure and energy density of DE and  is an EoS parameter which is useful to describe cosmic acceleration. A number of authors [7][8][9][10][11][12][13][14][15] have studied binary mixture of perfect fluid (PF) and anisotropic DE for Bianchi type-I, II, III, V, VI0, plane symmetric, kaluza-klein as well as higher dimensional cosmological models too. Recently, the anisotropic dark energy has been studied for Bianchi type-IX space-time [16].…”
Section:   Pmentioning
confidence: 99%
“…Recently, Asseo and Sol [13] and Roy & Banerjee [14] stressed the importance of B-type-II and proscribed LRS cosmological model. Kumar and Akarsu [15] mentioned B-type-II universe with anisotropic dark energy and perfect fluid. Wang [16]− [18] has investigated the models of Letelier-type within the theoretical account of LRS B-type-II.…”
Section: Introductionmentioning
confidence: 99%